Causes behind slow learners’ achievements and perspective at the primary schools - Gaid, Saida (My University, 2017)
My study attempts to look for the reasons behind slow learning of children at primary schools, and its impact on their achievement. It aims to create a sense of awareness in our schools concerning slow learners. A try is made to seek whether individual teachers are interested in developing many effective techniques and strategies for supporting those learners or not. In order to achieve these aims, we have started with shedding the light on some theories and perspectives that are related to slow learning in the introductory chapter; moving to the second one in which we relied on two main methods. They are questionnaire submitted to numbers of teachers at different primary schools, and interview done with parents of three slow learners in order to gather the necessary data about their views toward this category of learners. The results obtained reveal that there are many reasons that lead a student to be slow in learning. The main reason is the neglect of his parents especially at the periods of infancy and preschool because they are regarded as the main periods of child’s intellectual growth and development. Moreover, this difficulty which is slow learning surely affects their achievement in negative way depending on what we have reached (their results at school). Considering teachers and parents as the core reason of child’s slow learning is what we eventually came to discover, because both parents and teachers take an integral part in student’s success in learning. On the other hand, their relationship with them directly impacts their learning outcomes. Children officially need the ooperation between teacher’s professional development and parental involvement in the improvement of their learning skills.
case study : primary level in Tessimsilt
Keywords: Slow learning of children; Techniques for succes; Impact achievement